THE RELATIONSHIP BETWEEN AIR POLLUTION AND CORONARY ARTERY DISEASE: A SYSTEMATIC REVIEW - Rioza, Balqis Ufairah; Yudhie Tanta; Zulissetiana, Eka Febri (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Several previous research studies have shown that air pollution has broad impacts on human health, particularly in the cardiovascular field. Exposure to air pollution entering the respiratory system can trigger inflammatory responses and increase the risk of cardiovascular diseases such as coronary artery disease. This systematic review aim to determine the relationship between air pollution and the occurrence of Coronary Artery Disease (CAD). Journal searches were conducted on five electronic databases, namely Pubmed, Science Direct, Europe PMC, Wiley Online Library, and Cochrane, following the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) method. The search results get six original articles that meet the inclusion and exclusion criteria for analysis. Based on the results of the analysis shows that there is a significant relationship between air pollution in the form of gas components or particulate matter with the incidence of coronary artery disease. High levels of air pollution in an area can also increase the risk of CAD higher than areas with lower levels of air pollution.